A reliability-constrained cost-effective model for optimal sizing of an autonomous hybrid solar/wind/diesel/battery energy system by a modified discrete bat search algorithm - Shivaie, Mojtaba; Mokhayeri, Mohammad; Kiani-Moghaddam, Mohammad; Ashouri-Zadeh, Alireza (Solar energy, 2019)
•A new reliability-constrained cost-effective model is developed for optimal sizing of an AHRS.•A new non-deterministic framework is proposed to deal with uncertainty in load demand and inherent characteristics of solar and wind generations.•The practical considerations pertaining to the optimal sizing of an AHRS are considered.•A new hybrid of the MD-BAT and MCSM is used to solve the proposed model. During recent years, the optimal sizing of an autonomous hybrid energy system for microgrids operation management has been extensively explored. In this paper, with a new point of view, a reliability-constrained cost-effective model is developed to identify optimal sizing of an autonomous hybrid renewable system (AHRS). The significant aims of the proposed model are not only to address an exhaustive model for the AHRS by incorporating solar panel, wind turbine, diesel generator, and battery storage components, but also to implement practical considerations on the AHRS by considering its probabilistic characteristics. To do so, the proposed model takes into account total investment cost, the total fuel cost of the diesel generator, total maintenance cost and total expected load shedding cost in the optimization as four problem objectives subject to technical and operational constraints. A modified discrete bat search algorithm is widely employed to obtain the final optimal solution and followed by a Monte Carlo simulation method to handle non-deterministic characteristics pertaining to load demand, solar and wind generations. The obtained results of the proposed model are given and meticulously evaluated. These results show the feasibility and capabilities of the newly proposed model in the optimal sizing of an AHRS when compared with other approaches.